Analysis and Design Wireless Network and Security Based On Firewall In Pit Mining Area PT ABC - Yanto Setiawan; Agustiawan Sembiring; Muhammad Arif; Wihdayati Wihdayati (Syntax Corporation, 2022)
The 4.0 Industrial revolution has entered the mining industry. One of them is the application of big data technology in PT ABC, a coal mining contractor in Indonesia. To support the project's performance, an extensive internet connection covering certain areas, including pit areas, is needed. However, there are areas outside the GSM or Wi-Fi service in PT ABC District XYZ. To solve the issue, proper planning and analysis of Wi-Fi network coverage development and firewall-based wireless security are needed to support the operational of big data technology in the company's internal system. The planning and development of this network coverage and wireless security use the Network Development Life Cycle (NDLC) method. This method is useful to continue the improvement on wireless network in PT XYZ. The benefit of the NDLC method is that when someday an alteration is needed on the network, life cycle data has been recorded in the NDLC method. The result of this study is a design that can fix or cover the deficiency of the existing network condition. The design is in the form of Access Point placement design and access network settings using wireless security.